Koselleck, Danto and Total History - Shain, Ralph (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This paper argues that there are still lessons that theorists of history can learn from the linguistic turn in philosophy–in particular from its most influential practitioner, Wittgenstein. I take a Wittgensteinian approach in examining the concept of “total history” as it appears in the work of Koselleck and Danto. I argue that the concept is a pseudo-concept which has effects on their work even though each argues for the impossibility of its achievement. The implications are drawn for considering history as ongoing inquiry and the multiplicity of the types of questions that history seeks to answer. This approach avoids philosophical pseudo-problems and is a more assured way of establishing “history in the plural”, the phrase that has become attached to Koselleck’s work by his partisans.